The Effect of Liquidity, Capital Structure, and Profitability on Dividend Policy Moderated by Company Size in Industrial Sector Companies - Anisa Safitri; Eka Yulianti (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study analyzes the effect of liquidity, capital structure, and profitability on dividend policy with company size as a moderating variable in consumer goods industry sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. This study uses a quantitative approach with descriptive and associative methods. Data were obtained from the company's financial and annual reports, analyzed using Microsoft Excel and EViews. The sample consisted of 19 companies selected through the Non-Probability Sampling technique, with a total of 95 observations. The results of the analysis show that the classical assumption test has been met, including data normality, free from heteroscedasticity, multicollinearity, and autocorrelation. Partially, liquidity and capital structure have no effect on dividend policy, while profitability has a positive effect. Company size is unable to moderate the relationship between independent variables and dividend policy. These findings indicate that financial factors remain dominant in determining dividend policy, but future research is advised to consider non-financial factors and a longer period to obtain more accurate results.